Flora Ficológica do Médio Rio Xingu (Altamira, Pará, Brasil): Cyanobacteria - LIMA, Lucas Rodrigues (2025)
The objective of this work was to present a didactic product composed of a digital book to document the knowledge about the cyanobacteria present in the Middle Xingu River, and thus facilitate the identification of cyanobacteria species in practical classes of the curricular components of the Degree in Biological Sciences/ Altamira Campus related to this theme and also serve as reference literature for other scientific works.